Quercetin ameliorates chlorpyrifos‐induced oxidative stress in the rat brain: Possible involvment of PON2 pathway. Issue 3 (28th February 2018) - Ghahremani, Saeed; Soodi, Maliheh; Atashi, Amir
Abstract: In the present study, protective effect of quercetin against chlorpyrifos‐induced oxidative stress in the brain of rat and possible involvement of paraoxanase2 (PON2) pathway was investigated. The experimental groups include control, CPF (10 mg/kg), quercetin (20 mg/kg), and CPF + quercetin. All treatments were orally administered once per day for 1 month. The PON2 gene expression in brain was quantified by real time PCR method and oxidative stress markers in the brain and AChE activity in the brain and serum were measured. AChE activity significantly decreases in the brain and serum of CPF‐treated groups indicating CPF exposure. Quercetin restored the increased lipid peroxidation and decreased antioxidant enzyme activities and total thiol content which were induced by CPF. These results indicate the reduction of oxidative stress by quercetin. Also, quercetin unregulated the expression of PON2 gene more potently in CPF‐treated group. Practical applications: PON2 is a lactonase expressed in brain and has antioxidant and anti‐inflammatory activities. It is reported that quercetin, a flavonoid with antioxidant and neuroprotective activities, increases expression of paraoxanase2 enzyme (PON2) in cultured neural cells which resulted in neuroprotection against oxidative insults. Chlorpyrifos (CPF) is a neurotoxic organophosphate pesticide which can induce oxidative damage in the brain and trigger neurodegeneration. The aim of the present study was to evaluate the protective effect of quercetin against CPF‐induced oxidative stress in the brain of rat and possible involvement of PON2 pathway was also investigated. Results of the present study indicate that quercetin improves CPF‐induced oxidative stress and this effect may be achieved through upregulation of PON2 gene and potentiation of cellular antioxidant defense. Therefore, quercetin can be used as a dietary supplement to people at risk for CPF exposure such as farmers in order to reduce CPF‐induced brain oxidative damage and consecutive disorders.